Analisis Maturity Level Business Goals 8 Menggunakan COBIT Pada PT. APLIN - Ambarwati, Awalludiyah; Habibi, Ade Putra (Universitas Nusantara PGRI Kediri, 2017)
PT. APLIN is one of the companies engaged in the Information and Communication Technology (ICT) that serves a variety of customer needs in terms of communication and networking. The dynamic development of IT (Information Technology) resulted in changes in customer needs. PT. APLIN is updating regularly used IT and strives to provide services to meet customer needs. This research was conducted using COBIT 4.1 framework to find out maturity level in four IT process ie PO3 (Determining Technology Direction), AI5 (Procurement of IT Resources), DS2 (Managing Third Party Service) and DS6 (Identifying and Allocating Fees). Where these four IT processes are part of the business goals of achieving cost optimization from service delivery in the customer's perspective. The results showed that the maturity level was at the level of Repeatable but Intuitive for TI processors PO3, DS2 and DS6. While the IT AI5 process is at the Defined level. Planning mechanism of IT resource procurement and budget planning at PT. APLIN is appropriate and well documented. Companies need to improve IT infrastructure development mechanisms and maintain vendor performance relationships or third parties.